Heparin is required for the formation of granules in connective tissue mast cells - Herrera-Heredia, Sandra Abril; Hsu, Hsuan-Po; Kao, Cheng-Yen; Tsai, Yu-Huan; Yamaguchi, Yu; Roers, Axel; Hsu, Chia-Lin; Dzhagalov, Ivan L. (Frontiers in Immunology, 2022)
Mast cells are innate immune cells strategically positioned around blood vessels near body surfaces. Their primary weapons are bioactive amines, mast cell-specific proteases, and cytokines stored in preformed granules. Mast cells granules constituents are packaged efficiently with the help of the highly negatively charged Heparan sulfate-derivative, Heparin. Heparin is one of the most widely used drugs to treat coagulation disorders, yet, it is not found in the circulation at a steady state, casting doubt that the prevention of blood clotting is its physiological function. Early studies using Ndst2-/- mice have shown that Heparin is essential for mast cells granules formation. However, these mice could still produce less sulfated Heparan sulfate that could potentially replace Heparin. Here, we have created and validated a novel genetic model for Heparin deficiency, specifically in connective tissue mast cells, to address the physiological role of this molecule. Using this model, we have demonstrated that Heparin is required for mast cell granules formation; without it, mast cells are reduced in the peritoneal cavity and the skin. The absence of Heparin impaired the response to passive cutaneous anaphylaxis but, surprisingly, enhanced ear swelling in an irritant dermatitis model and reduced the lesion size and bacterial burden in a Staphylococcus aureus necrotizing dermatitis model. The altered function of Heparin-deficient mast cells in the latter two models was not mediated through enhanced Histamine or TNF-alpha release. However, the Mrgprb2 receptor was up-regulated in knock-out mast cells, potentially explaining the enhanced response of mutant mice to irritant and necrotizing dermatitis. Altogether our results expand our current understanding of the physiological role of Heparin and provide unique tools to further dissect its importance.